# How do you solve #3x^2 + 7x - 6 = 0#?

You get two solutions:

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the quadratic equation 3x^2 + 7x - 6 = 0, you can use the quadratic formula, which is x = (-b ± √(b^2 - 4ac)) / (2a). In this equation, a = 3, b = 7, and c = -6. Plug these values into the quadratic formula and solve for x.

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you solve #x^2=121#?
- How do you solve using the completing the square method #x^2 - 14x = 0#?
- How do you find the vertex and intercepts for #y=2(x+2)^2-13#?
- How do you find the vertex of a parabola #y= [x-4]^2#?
- How do I use the vertex formula to determine the vertex of the graph for #y=x^2+4x+1#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7